2013
DOI: 10.12659/ajcr.889291
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial metastasis from primary anorectal melanoma

Abstract: Patient: Male, 64Final Diagnosis: Metastatic anorectal melanoma with endotracheal metastasisSymptoms: Fatigue • weight loss • hematochezia • coughMedication: NoneClinical Procedure: Biopsy of anal mass • rigid bronchoscopySpecialty: Internal medicine • oncology • pulmonologyObjective:Rare diseaseBackground:Anorectal melanoma is a rare cancer with a poor prognosis. The mean survival after diagnosis is 15–25 months. At the time of diagnosis, 61% of patients have local regional lymph node metastases, and 21% have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Cutaneous malignant melanoma (CMM) originates from melanocytes and is a highly aggressive disease, accounting for 80% of deaths arising from skin cancer worldwide [ 1 ]. CMM is highly characteristic of aggressive invasion, early metastasis, and resistance to chemotherapy or radiotherapy, which results in increased incidence and mortality worldwide [ 2 , 3 ]. Despite improvements in early CMM diagnosis, the 5-year survival rate for patients with advanced disease is still very low [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous malignant melanoma (CMM) originates from melanocytes and is a highly aggressive disease, accounting for 80% of deaths arising from skin cancer worldwide [ 1 ]. CMM is highly characteristic of aggressive invasion, early metastasis, and resistance to chemotherapy or radiotherapy, which results in increased incidence and mortality worldwide [ 2 , 3 ]. Despite improvements in early CMM diagnosis, the 5-year survival rate for patients with advanced disease is still very low [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The principles of conservative management of air leaks include air drainage by the use of chest tubes and treatment of infection and nutrition deficits [ 5 ]. Currently, with the evolution of endoscopic methods [ 6 , 7 ], the endobronchial management of air leaks has become an alternative therapy to treat persistent air leaks. Interventional bronchoscopy may be a valuable alternative in the treatment of BPFs, especially at distal tracts of the bronchial tree, and could be an ideal therapeutic option for high-risk patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that the effect of interventional bronchoscopy for endobrochial metastases from malignant neoplasm, resolving endometrial metastases from colorectal cancer 5 , small cell lung cancer 6 , renal cell carcinoma 7 , anorectal melanoma 8 and hypernephroma 9 . However, there is little information about interventional bronchoscopy for endobronchial metastasis from advanced leiomyosarcoma.…”
Section: Introductionmentioning
confidence: 99%